A web-based gamification program to improve nutrition literacy in families of 3- to 5-year-old children: the Nutriscience Project - Azevedo, José (2019)
Objective: Assess the impact of a web-based gamification program on nutrition literacy of families and explore differences in impact by socioeconomic status. Design: Quasi-experimental. Setting: Thirty-seven kindergartens from Portugal. Participants: Eight hundred seventy-seven families. Intervention: Web-based social network of participants' interactions, educational materials, apps and nutritional challenges, focused on fruit, vegetables, sugar, and salt. Main Outcome Measures: Parental nutrition literacy (self-reported survey − 4 dimensions: Nutrients, Food portions, Portuguese food wheel groups, Food labeling). Analysis: General linear model − Repeated measures was used to analyze the effect on the nutrition literacy score. Results: Families uploaded 1267 items (recipes, photographs of challenges) and educators uploaded 327 items (photographs, videos) onto the interactive platform. For the intervention group (n = 106), the final mean (SD) score of nutrition literacy was significantly higher than the baseline: 78.8% (15.6) vs 72.7% (16.2); P<.001, regardless of parental education and perceived income status. No significant differences in the scores of the control group (n = 83) were observed (final 67.8% [16.1] vs initial 66.4% [15.6]; P= .364). Conclusions and Implications: Gamified digital interactive platform seems to be a useful, easily adapted educational tool for the healthy eating learning process. Future implementations of the program will benefit from longer time intervention and assessment of the eating habits of families before and after intervention.